Simultaneous edited MRS of GABA, glutathione, and ethanol. (14th January 2020) - Saleh, Muhammad G.; Wang, Min; Mikkelsen, Mark; Hui, Steve C.N.; Oeltzschner, Georg; Boissoneault, Jeff; Stennett, Bethany; Edden, Richard A.E.; Porges, Eric C.
Abstract : The aim of this work was to develop simultaneous edited MRS of γ‐aminobutyric acid (GABA), glutathione (GSH), and ethanol (EtOH) using Hadamard encoding and reconstruction of MEGA‐edited spectroscopy (HERMES) at 3T. Density‐matrix simulations of HERMES were carried out and compared with phantom experiments. In vivo experiments were performed in six healthy volunteers about 30 min after alcohol consumption. Simulations of HERMES showed GABA‐, GSH‐, and EtOH‐edited spectra with low levels of crosstalk and excellent agreement with phantom spectra. In vivo experiments showed well edited GABA signals at 3.0 ppm, GSH at 2.95 ppm, and EtOH at 1.18 ppm in the respective Hadamard combination spectra. Measured integral ratios were 0.082 ± 0.012 for GABA/Cr, 0.037 ± 0.006 for GSH/Cr, and 0.305 ± 0.129 for EtOH/Cr. Simulated, phantom, and in vivo measurements of HERMES show excellent separation of GABA‐, GSH‐, and EtOH‐edited signals with negligible levels of crosstalk. HERMES allows a threefold acceleration of editing while maintaining spectral quality compared with sequentially acquired MEGA‐PRESS measurements. Abstract : We demonstrate simultaneous edited MRS of γ‐aminobutyric acid (GABA), glutathione (GSH), and ethanol (EtOH) using Hadamard encoding and reconstruction of MEGA‐edited spectroscopy (HERMES) at 3T. HERMES allows threefold acceleration of editing while maintaining spectral quality compared with sequentially acquired MEGA‐PRESS measurements.